Thrombospondin-1: Multiple Paths to Inflammation - Zenaida Lopez-Dee; Kenneth Pidcock; Linda S. Gutierrez (Hindawi Limited, 2011)
Inflammation is a defensive process against tissue injury. Once this self-protective strategy is initiated, an effective resolution of the process is crucial to avoid major and unnecessary tissue damage. If the underlying event inducing inflammation is not addressed and homeostasis is not restored, this process can become chronic and lead to angiogenesis and carcinogenesis. Thrombospondin-1 (TSP-1) is a matricellular protein involved in angiogenesis, cancer, and inflammation. The effects of TSP-1 have been studied in many preclinical tumor models, and mimetic peptides are being tested in cancer clinical trials. However, the molecular mechanisms explaining its role in inflammatory processes are not well understood. This paper will discuss the role of TSP-1 in inflammation and its interaction with key receptors that may explain its functions in that process. Recent literature will be reviewed showing novel mechanisms by which this multifaceted protein could modulate the inflammatory process and impact its resolution.